Moonlight mile [videorecording (DVD)] - Silberling, Bradley; Gyllenhaal, Jake, 1980-; Hoffman, Dustin, 1937-; Sarandon, Susan, 1946-; Pompeo, Ellen; Hunter, Holly, 1958- (Touchstone Home Entertainment ; Buena Vista Home Entertainment, 2003)
Set in the early '70s, Joe is distraught after the death of his fiancée. He moves in with her parents, Ben and JoJo, while trying to sort out all of the legal troubles and painful details of the wedding cancellations. While trying to locate the wedding invitations in the mail, Joe meets Bertie, whose boyfriend has been MIA in Vietnam. Despite his growing relationship with his late fiancée's parents, Joe begins to foster a romance with Bertie.